2021
DOI: 10.1186/s13063-021-05072-4
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/II Clinical Trial to evaluate the efficacy of baricitinib to prevent respiratory insufficiency progression in onco-hematological patients affected with COVID19: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives Baricitinib is supposed to have a double effect on SARS-CoV2 infection. Firstly, it reduces the inflammatory response through the inhibition of the Januse-Kinase signalling transducer and activator of transcription (JAK-STAT) pathway. Moreover, it reduces the receptor mediated viral endocytosis by AP2-associated protein kinase 1 (AAK1) inhibition. We propose the use of baricinitib to prevent the progression of the respiratory insufficiency in SARS-CoV2 pneumonia in onco-haematologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“… 109 Another observational cohort study from Spain showed that baricitinib improved lung function in patients with moderate-to-severe COVID-19 receiving corticosteroid treatment. 312 Interestingly, existing studies showed that besides the acknowledged inhibitory effects on CS, baricitinib can also dampen ACE2-mediated SARS-CoV-2 endocytosis by inhibiting AP2-associated protein kinase 1 and cyclin G-associated kinase, 313 , 314 which serves as another mechanism of its action in COVID-19. Moreover, several other reports have also been published, 313 , 315 – 322 and numerous clinical trials of baricitinib are registered at ClinicalTrials.gov to evaluate its clinical effects in severe COVID-19.…”
Section: Blockade Of Signaling Pathwaysmentioning
confidence: 99%
“… 109 Another observational cohort study from Spain showed that baricitinib improved lung function in patients with moderate-to-severe COVID-19 receiving corticosteroid treatment. 312 Interestingly, existing studies showed that besides the acknowledged inhibitory effects on CS, baricitinib can also dampen ACE2-mediated SARS-CoV-2 endocytosis by inhibiting AP2-associated protein kinase 1 and cyclin G-associated kinase, 313 , 314 which serves as another mechanism of its action in COVID-19. Moreover, several other reports have also been published, 313 , 315 – 322 and numerous clinical trials of baricitinib are registered at ClinicalTrials.gov to evaluate its clinical effects in severe COVID-19.…”
Section: Blockade Of Signaling Pathwaysmentioning
confidence: 99%
“…A phase Ib/II trial, BARCOVID19 (50), in Barcelona, Spain is expected to recruit 136 participants with the main objective of determining the tolerability of baricitinib in oncohematological patients with COVID-19 in phase I. The phase II of this trial aims to determine the reduction of inflammatory response due to COVID-19, and prevention of development of severe ARDS in oncohematological patients compared to the other treatment received at the discretion of the investigator.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a phase-3, global, double-blind, randomized, placebo-controlled trial by Marconi and colleagues, COVID-19 patients received the corticosteroid dexamethasone, in combination with Baricitinib or placebo. The investigators reported that although reduced disease progression did not achieve statistical significance, mortality rate was reduced by 38.2% in patients that received the combined treatment (170). This promising path could be further examined in clinical trials that include individuals with DS, as JAK1/2 inhibition may be even more beneficial in COVID-19 patients with DS.…”
Section: Aberrant Cytokine and Chemokine Signaling In Dsmentioning
confidence: 99%